Response to Infection by Trypanosoma cruzi in a Murine Model - De Alba-Alvarado, Mariana; Bucio-Torres, Martha Irene; Zenteno, Edgar; Sampedro-Carrillo, Enrique; Hernández-Lopez, Mariana; Reynoso-Ducoing, Olivia; Torres-Gutiérrez, Elia; Guevara-Gomez, Yolanda; Guerrero-Alquicira, Raquel; Cabrera-Bravo, Margarita; Salazar-Schettino, Paz María (Frontiers in Veterinary Science, 2020)
Cardiopathy is a common, irreversible manifestation of the chronic phase of Chagas disease; however, there is controversy as to how the causes for progression from the acute to the chronic phase are defined. In this work, the presence of the parasite is correlated with the occurrence of cell infiltration and fibrosis in cardiac tissues, as well as IgG detection and disease progression in a murine model. Fifty CD1 mice were infected intraperitoneally with Trypanosoma cruzi, while 30 control were administered with saline solution. Parasitemia levels were determined, and IgG titers were quantified by ELISA. At different times, randomly selected mice were euthanized, and the heart was recovered. Cardiac tissue slides were stained with HE and Masson trichrome stain. A significant increase in parasitemia levels was observed after 15 days post-infection (dpi), with a maximum of 4.1 × 106 parasites on 33 dpi, ending on 47 dpi; amastigote nests were observed on 15-62 dpi. Histological analysis revealed lymphocytic infiltration and fibrotic lesions from 8 dpi until the end of the study, on 100 dpi. The presence of plasma cells in the myocardium observed on 40-60 dpi, accompanied by seropositivity to ELISA on 40-100 dpi, was regarded as the hallmark of the transition phase. Meanwhile, the chronic phase, characterized by the absence of amastigotes, presence of cell infiltration, fibrotic lesions, and seropositivity, started on 62 dpi. A strong correlation between parasitemia and the presence of amastigote nests was found (r = 0.930), while correlation between the presence of fibrosis and of amastigote nests was weak (r = 0.306), and that between fibrosis and lymphocyte infiltration on 100 dpi was strong (r = 0.899). The murine model is suitable to study Chagas disease, since it can reproduce the chronic and acute phases of the human disease. The acute phase was determined to occur on 1-62 dpi, while the chronic phase starts on 62 dpi, and fibrotic damage is a consequence of the continuous inflammatory infiltration; on the other hand, fibrosis was determined to start on the acute phase, being more apparent in the chronic phase, when Chagas disease-related cardiopathy is induced.